Efeito da salinidade da água do mar no rendimento, composição e atividades biológicas de frações polissacarídicas da Chlorophyta Caulerpa cupressoides var. flabellata - Costa, Mariana Santana Santos Pereira da (2010)
Seaweeds sulfated polysaccharides have been described as having various pharmacological activities. However, nothing is known about the influence of salinity on the structure of sulfated polysaccharides from green seaweed and pharmacological activities they perform. Therefore, the main aim of this study was to evaluate the effect of salinity of seawater on yield and composition of polysaccharides-rich fractions from green seaweed Caulerpa cupressoides var. flabellata, collected in two different salinities beaches of the coast of Rio Grande do Norte, and to verify the influence of salinity on their biological activities. We extracted four sulfated polysaccharides-rich fractions from C. cupressoides collected in Camapum beach (denominated CCM F0.3; F0.5; F1.0; F2.0), which the seawater has higher salinity, and Buzios beach (denominated CCB F0.3; F0.5; F1.0; F2.0). Different from that observed for other seaweeds, the proximate composition of C. cupressoides did not change with increased salinity. Moreover, interestingly, the C. cupresoides have high amounts of protein, greater even than other edible seaweeds. There was no significant difference (p>0.05) between the yield of polysaccharide fractions of CCM and its CCB counterparts, which indicates that salinity does not interfere with the yield of polysaccharide fractions. However, there was a significant difference in the sulfate/sugar ratio of F0.3 (p<0.05) and F0.5 (p<0.01) (CCM F0.3 and CCB F0.5 was higher than those determined for their counterparts), while the sulfate/sugar ratio the F1.0 and F2.0 did not change significantly (p>0.05) with salinity. This result suggested that the observed difference in the sulfate/sugar ratio between the fractions from CCM and CCB, is not merely a function of salinity, but probably also is related to the biological function of these biopolymers in seaweed. In addition, the salinity variation between collection sites did not influence algal monosaccharide composition, eletrophoretic mobility or the infrared spectrum of polysaccharides, demonstrating that the salinity does not change the composition of sulfated polysaccharides of C. cupressoides. There were differences in antioxidant and anticoagulant fractions between CCM and CCB. CCB F0.3 (more sulfated) had higher total antioxidant capacity that CCM F0.3, since the chelating ability the CCM F0.5 was more potent than CCB F0.5 (more sulfated). These data indicate that the activities of sulfated polysaccharides from CCM and CCB depend on the spatial patterns of sulfate groups and that it is unlikely to be merely a charge density effect. C. cupressoides polysaccharides also exhibited anticoagulant activity in the intrinsic (aPTT test) and extrinsic pathway (PT test). CCB F1.0 and CCM F1.0 showed different (p<0,001) aPTT activity, although F0.3 and F0.5 showed no difference (p>0,05) between CCM and CCB, corroborating the fact that the sulfate/sugar ratio is not a determining factor for biological activity, but rather for sulfate distribution along the sugar chain. Moreover, F0.3 and F0.5 activity in aPTT test was similar to that of clexane®, anticoagulant drug. In addition, F0.5 showed PT activity. These results suggest that salinity may have created subtle differences in the structure of sulfated polysaccharides, such as the distribution of sulfate groups, which would cause differences in biological activities between the fractions of the CCM and the CCB